COVID-19 booster enhances IgG mediated viral neutralization by human milk in vitro - Valcarce, Vivian; Stafford, Lauren Stewart; Neu, Josef; Parker, Leslie; Vicuna, Valeria; Cross, Tyler; D'Agati, Olivia; Diakite, Sisse; Haley, Addison; Feigenbaum, Jake; Al Mahmoud, Mahmoud Y.; Visvalingam, Anjali; et al. (Frontiers in Nutrition, 2024)
Facilitated by the inability to vaccinate, and an immature immune system, COVID-19 remains a leading cause of death among children. Vaccinated lactating mothers produce specific SARS-CoV-2 antibodies in their milk, capable of neutralizing the virus in vitro. Our objective for this study is to assess the effect of COVID-19 booster dose on SARS-CoV-2 antibody concentration and viral neutralization in milk, plasma, and infant stool.Thirty-nine mothers and 25 infants were enrolled from December 2020 to May 2022. Milk, maternal plasma, and infants' stool were collected at various time-points up to 12 months following mRNA COVID-19 vaccination. A subgroup of 14 mothers received a booster dose. SARS-CoV-2 antibody levels and their neutralization capacities were assessed.Booster vaccination led to significantly higher IgG levels within human milk and breastfed infants' stool. In vitro neutralization of VSV-gfp-SARS-CoV-2-S-gp, VSV-SARS-CoV-2-S-gp a laboratory safe SARS-CoV-2 like pseudovirus, infection improved following the booster, with a 90% increase in plasma neutralization and a 60% increase in milk neutralization. We found that post-booster neutralization by human milk was highly correlated to SARS-CoV-2 IgG level. In support of our correlation result, Protein G column depletion of IgG in milk yielded a significant reduction in viral neutralization (p-value = 0.04).The substantial increase in neutralizing IgG levels in milk and breastfed infants' stool postbooster, coupled with the decrease in milk neutralization capabilities upon IgG depletion, underscores the efficacy of booster doses in augmenting the immune response against SARS-CoV-2 in human milk.